Popov S.N., Antoniuk D.A. Analytical model of geometric components solid phase calculation of wear resistant alloys in contact conditions with fixed abrasives. - Попов, С.М.; Антонюк, Д.А. (Problems of Tribology, 2014)
The paper attempts to solve the complex problem of developing algorithms and analytical models for calculating geometric components of the solid phase of wear-resistant alloys in contact with fixed abrasive that can be used to identify relationships between strengthens phase and abrasive according to the principle Sharpe.The research allowed to improve and adapt the analytical model of abrasive wear by the interaction of worker body (coated with heterogeneous alloys containing strengthens phase and matrix) in a fixed (granite particle) contact abrasion damage. Thus, the graphical interpretation of the analytical model allows within practical to determine the adequacy, optimal ratio between the diameter of the abrasive particles and the size of strengthens phase. In addition, the proven ability of the analytical calculation of distances between the centers of excess solids strengthens phase heterogeneous alloys. Therefore, the analysis of simulation results based on graph-analytic model of modernized revealed that the amount of reinforcing phase of 65 - 70 %, the optimum distance between the particles of the solid phase is 4,0 - 4,21 m;Analysis calculations predict the optimal number, type of strengthens phase, taking into account its spatial location, which crystallizes in alloys in grand total allowed receive the quantitative assessment of fracture intensity depending on the tribological and tribotechnical factors of operation:- number of matrix and strengthens phase is determined from the density materials (ρу.ф., ρм), the number of layers of strengthens material and the angle of interaction tools with abrasive β.- the smallest wear considering minimum required mass particle of strengthens phase obtained in interaction angles 30 - 45° and 65 - 80°.